Declaraciones del Comité Internacional de Directores de Revistas Médicas anexas a las normas de Vancouver - of Medical Journal Editors, International Committee (Revista Médica Herediana, 2013)
These statements, which are published by the International Committee of Medical Journal Editors in conjunction with the Vancouver standards, cover sorne of the legal, ethical, and practical aspects of the publication of research papers, and of the comments generated by them, in biomedical journals. Pollowing a definition of what constitutes a peer-reviewed journal, the roles of journal owners and editors are described, along with those of members of an editorial board, and procedural norms are set forth in connection with conflicts of interests, retractions or corrections, fraud, and breaches of confidentiality. Arnong the last topics explored are the problems involved in the dissemination of research results by the popular media, the handling of advertising within the journal, and the simultaneous acceptance of manuscripts whose authors have arrived at opposite conclusions regarding the results of a particular study.